2017
DOI: 10.1212/nxg.0000000000000129
|View full text |Cite
|
Sign up to set email alerts
|

A gain-of-function mutation in the GRIK2 gene causes neurodevelopmental deficits

Abstract: Objective:To identify inherited or de novo mutations associated with a suite of neurodevelopmental abnormalities in a 10-year-old patient displaying ataxia, motor and speech delay, and intellectual disability.Methods:We performed whole-exome sequencing of the proband and her parents. A pathogenic gene variant was identified as damaging based on sequence conservation, gene function, and association with disorders having similar phenotypic profiles. Functional characterization of the mutated protein was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…This is what is observed (Supplementary Figure 3). Unusual current phenotypes strikingly similar to those described here with constitutive activation, outward shifted steady-state currents and large tail currents have been recently described for kainate receptors harboring clinically-relevant mutations in their transmembrane region 53 . These effects are best explained by profoundly altered gating properties - exquisite sensitivity to ambient agonist (i.e.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is what is observed (Supplementary Figure 3). Unusual current phenotypes strikingly similar to those described here with constitutive activation, outward shifted steady-state currents and large tail currents have been recently described for kainate receptors harboring clinically-relevant mutations in their transmembrane region 53 . These effects are best explained by profoundly altered gating properties - exquisite sensitivity to ambient agonist (i.e.…”
Section: Discussionsupporting
confidence: 82%
“…These effects are best explained by profoundly altered gating properties - exquisite sensitivity to ambient agonist (i.e. glutamate) and reopening of receptors as they recover from desensitization 53 , 54 —as we propose here for glycine excitatory GluN1/GluN3A receptors under reducing conditions. The GluN3A-C859-C913 disulfide bridge occupies a strategic location in GluN3A 12 , 55 , connecting the ABD lower lobe to the TMD ion channel 56 , 57 .…”
Section: Discussionmentioning
confidence: 67%
“…GRIK2 belongs to the kainate family of glutamate receptors that function as ligand-activated ion channels. This gene is highly expressed in brain and mutations in the gene have been associated with cortical development, autism and schizophrenia [60][61][62] . Interestingly, a large (6036 cases) genome-wide association study identified SNPs near GRIK2 as showing suggestive levels of association with longevity (OR = 1.2, p = 5.09e −8 ) 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al also suggested that GRIK2 gene was a candidate gene for epilepsy. Previously, some studies concluded that GRIK2 gene causes neurodevelopmental deficits and intellectual disability (ID) . GRIK2 was proposed as the genetic cause of isolated moderate to severe ID in an Iranian family .…”
Section: Discussionmentioning
confidence: 99%